Tracking of Resistant Salmonella Species in Poultry Farms: New Method of Control Using Essential Oils Nano-Emulsion Conjugated with Antimicrobial Agents - Salam, H. S. H.; Mohammed, A. N.; Hosni, A. R.; Shehata, A. A. E. (Tropical Animal Science Journal, 2021)
This work was designed to monitor and track Salmonella spp. in the different internal organs (heart, liver, spleen, and caecum) of 247 bird species (chickens n=176, chicks n=47, ducks n=15, and ducklings n=9) with variable ages in two governorates; El-Fayoum and Beni-Suef, Egypt. Besides assessing the antimicrobial activity of antibacterial agents, essential oils, oils nano-emulsion, and their interactions with each other against salmonellae isolates for their control at the farm level. All samples were collected aseptically for further microbiological and serological investigations. Moreover, the efficiency of essential oils and oils nano-emulsion (thymol, carvacrol, basil, and cinnamon) against recovered Salmonellae were tested using the agar dilution method. A total of fourteen Salmonella serotypes were detected from different investigated internal organs (heart, liver, and spleen), and the three most predominant serovars were S. virchow (17.14%), S. infantis (11.43%), and S. anatum (11.43%). The resistance profile of Salmonella spp. referred to 47.14%, 40.0%, 31.43%, 25.71%, 21.43%, 21.43%, and 21.43% against ampicillin, chloramphenicol, gentamicin, aztreonam, cefazolin, cefotaxime, and tobramycin, respectively. The ability of essential oils (carvacrol oil 0.01%, basil 0.1%, cinnamon 0.01%, and thymol oil 0.01%) to inhibit the growth of Salmonellae differed significantly at 34.29%, 17.14%, 11.43%, and 1.43%, respectively (p<0.05). Oppositely, essential oils nano-emulsion (thymol 0.01%, carvacrol 0.001%, basil 0.1%, and cinnamon 0.01%) showed no inhibitory effect on the growth of Salmonella species. In conclusion, the interactive action between essential oils and antimicrobial agents approved the ability to enhance the susceptibility of the resistant Salmonella isolates against gentamicin, tobramycin, chloramphenicol, and cefazolin. In addition, the interactive action between essential oils nano-emulsion and antimicrobial agents on resistant Salmonella isolates revealed a complete enhanced effect against cefotaxime and variable enhancement against aztreonam.